2022
DOI: 10.1002/sstr.202200263
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Ni–Fe and Ni–Co Metal–Organic Frameworks for Electrocatalytic Water‐Splitting Reactions

Abstract: Scheme 2. Reported synthesis strategies for the preparation of Ni-based transition metal MOFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…As summarized by a number of previous review articles, a large number of synthesis routes have been designed for the metal-ion doping of MOFs. [30][31][32][33][34][35][36] However, because the main goal of this frontier article is to summarize the influence of metal-ion doping on the electronic structure and local coordination of MOFs and explain how this affects their catalytic performance for the OER, we focus only on the one-pot synthesis route, which is the most common and most straightforward approach for introducing heteroatoms to the crystal lattice of frameworks. 37 This approach has also been widely used for the deposition of binder-free MOF thin films on the surface of an electrically conducting substrate that can be employed directly as an electrode in a water-splitting electrolyser.…”
Section: Metal-ion Doping and Mof Film Formation Strategy For Water S...mentioning
confidence: 99%
“…As summarized by a number of previous review articles, a large number of synthesis routes have been designed for the metal-ion doping of MOFs. [30][31][32][33][34][35][36] However, because the main goal of this frontier article is to summarize the influence of metal-ion doping on the electronic structure and local coordination of MOFs and explain how this affects their catalytic performance for the OER, we focus only on the one-pot synthesis route, which is the most common and most straightforward approach for introducing heteroatoms to the crystal lattice of frameworks. 37 This approach has also been widely used for the deposition of binder-free MOF thin films on the surface of an electrically conducting substrate that can be employed directly as an electrode in a water-splitting electrolyser.…”
Section: Metal-ion Doping and Mof Film Formation Strategy For Water S...mentioning
confidence: 99%
“…In recent years, metal-organic porous frameworks (MOFs) have emerged as an important class of materials for catalysis/ electrocatalysis because their porous structure is favourable for mass transport and exposing more active sites. [17][18][19][20][21][22] The metal ion coordination geometry and versatility of organic linkers have been exploited to construct MOFs with varied porosity and functionality. 23,24 In spite of their structural and functional versatility, only limited MOFs have been explored for electrocatalytic activity due to their poor stability in aqueous medium especially under acidic/alkaline conditions and low conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Constructing hetero bimetallic MOFs, generation of non-coordinated metal sites, labile solvent coordination and engineering intermetallic distances are some of the other methods reported for improving the electrocatalytic activity of MOFs. [35][36][37][38][39][40][41][42][43][44][45][46][47][48] However, the clear design strategy and direct use of MOFs as efficient electrocatalysts are still in the early stages. Optimizing the electronic structure of the metal catalytic centre is the most straightforward method to modify the intrinsic properties of the catalyst including the electronic conductivity and reaction energy barrier.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs and MOF-derived catalysts have been studied for many electrochemical reactions, including hydrogen evolution, oxygen reduction, , and oxygen evolution reaction. Unfortunately, MOFs can be unstable during electrochemical reactions such as the OER and may convert to (oxy)­hydroxides. For example, Zhao et al demonstrated the structural transformations of Ni 0.5 Co 0.5 -MOF-74 to Ni 0.5 Co 0.5 OOH during OER using operando X-ray absorption spectroscopy (XAS) . Recently, Yuan et al have designed metal-hydroxide organic frameworks (MHOFs) that are composed of edge-sharing metal-hydroxide octahedral sheets cross-linked with organic linkers, which show tunable metal redox potential and electrochemical OER activity via metal substitution .…”
Section: Introductionmentioning
confidence: 99%